AMPK-dependent phosphorylation of HDAC8 triggers PGM1 expression to promote lung cancer cell survival under glucose starvation. (28th May 2020) - Li, Yanping; Liang, Ronghui; Sun, Mingming; Li, Zhen; Sheng, Hao; Wang, Jiyan; Xu, Pengjuan; Liu, Shuangping; Yang, Wancai; Lu, Bin; Zhang, Shuai; Shan, Changliang
Abstract: Cancer cells undergo metabolic reprogramming to sustain their own survival under an environment of increased energy demand; however, the mechanism by which cancer cells ensure survival under glucose deprivation stressed conditions remains elusive. Here, we show that deprivation of glucose, dramatically activated the glycogen pathway, accompanied by elevated phosphoglucomutase 1 (PGM1) expression. We further identified that AMP-activated protein kinase (AMPK) stimulated PGM1 expression by inducing histone deacetylase 8 (HDAC8) phosphorylation. Moreover, we demonstrated that glucose deprivation-induced AMPK activation stimulated the translocation of HDAC8 from the nucleus to the cytoplasm, consequently disrupting the binding between HDAC8 and histone 3. PGM1 expression was also found to be critical for lung cancer glycolysis, the oxidative pentose phosphate pathway, and oxidative phosphorylation under glucose deprivation conditions, and further led to the aberrant expression of metabolic enzymes involved in glucose metabolism mediated by ERK1/2. Finally, PGM1 was found to be highly expressed in lung cancer tissues from patients, which correlated with a poor prognosis. Taken together, these results revealed that AMPK activation by glucose deprivation leads to enhanced PGM1 expression, an essential component of the metabolic switch, to facilitate cancer progression, suggesting PGM1 as promising anti-cancer treatment targets. Highlights: PGM1 expression is increased under glucose deprivation conditions mediated by activated AMPK. AMPK phosphorylated-HDAC8 upregulates histone H3 acetylation levels on PGM1 promoter. PGM1 alters the expression of glucose metabolism enzymes mediated by ERK1/2 signaling. PGM1 is more highly expressed in lung cancer tissues and correlates with poor prognosis.